1988
DOI: 10.1079/pns19880025
|View full text |Cite
|
Sign up to set email alerts
|

Gut transit and carbohydrate uptake

Abstract: Classical assessments of nutritional adequacy rely on tables of supposed nutrient requirements for animals or for man on the one hand, and the ability of feedstuffs to provide them on the other. These are expressed in gross or overall digestibility terms and do not relate to differences in the rates of amounts of digestion occumng in different parts of the gut. Yet in the case of carbohydrates, these differences in the pattern of digestion are factors which have a considerable bearing on animal growth, or huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…(3) Another possibility is that psyllium retains alimentary fats into the gastric lumen by modifying motor activity of the gastric muscle (Jenkins et al, 1978). Fat content Inhibition of food intake by psyllium D Rigaud et al is able to modify the effect of dietary ®bre on hunger (Low et al, 1988;Cummings et al, 1979). Unfortunately, we did not study the gastric emptying time of fats, because of the inaccuracy of the methods using labeled fat in mixed meal.…”
Section: Inhibition Of Food Intake By Psyllium D Rigaud Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…(3) Another possibility is that psyllium retains alimentary fats into the gastric lumen by modifying motor activity of the gastric muscle (Jenkins et al, 1978). Fat content Inhibition of food intake by psyllium D Rigaud et al is able to modify the effect of dietary ®bre on hunger (Low et al, 1988;Cummings et al, 1979). Unfortunately, we did not study the gastric emptying time of fats, because of the inaccuracy of the methods using labeled fat in mixed meal.…”
Section: Inhibition Of Food Intake By Psyllium D Rigaud Et Almentioning
confidence: 99%
“…It has been shown that the increased viscosity of the food obtained with soluble ®bres may further reduce the rate of small intestinal absorption. Indeed an increase in the viscosity of food may have several effects: (a) to slow down the small intestinal transit (Low, 1988;Cherbut et al, 1994); but Cummings et al (1979) did not ®nd any modi®cation of oro-cecal transit time with pectin; (b) to reduce the interaction between food nutrients and digestive enzymes (Flourie  et al, 1984;Cummings et al, 1979; to increase the time for nutrient diffusion, by increasing the thickness of the unstirred water layer (Flourie  et al, 1984;Rydning & Berstad, 1986). This is consistent with the studies which have demonstrated that soluble ®bres could decrease the area under the curve of serum glucose after a duodenal glucose load (Berggren et al, 1993).…”
Section: Inhibition Of Food Intake By Psyllium D Rigaud Et Almentioning
confidence: 99%
“…Cockroaches assimilate 95-98% of ingested glucose regardless of concentration (O.CM-l.Omoll" 1 ; Treherne, 1957). Humans digest and absorb essentially all ingested simple sugars (Low, 1988). Measurements of the refractive index of excreted fluid for painted lady butterflies (Vanessa cardui) indicate 96-98 % assimilation for 0.5-1.5moll" 1 sucrose (F. R. Hainsworth, in preparation).…”
Section: Concentration Comparisonsmentioning
confidence: 99%
“…Degradation of this flavonoid results in the production of 3,4-dihydroxyphenylacetic acid (DOPAC), which has antiproliferative activity in colon cancer cells (Schneider and Blaut, 2000; Schneider et al, 2000; Gao et al, 2006). Nevertheless, glucose is rapidly absorbed in the small intestine and negligible amounts reach the colon, where E. ramulus resides (Low, 1988).…”
Section: Introductionmentioning
confidence: 99%